Dog bite management practices by general practitioners; where are we standing in ASIA; a narrative review - Gillani, Syed Faraz Ul Hassan Shah; Memoona, Ayesha; Ehsan, Tauqeer (Journal of the Pakistan Medical Association, 2022)
Rabies is an infectious viral disease endemic worldwide and is fatal after the onset of clinical symptoms. In 99% of cases, dogs contribute to infectious viral transmission in humans. It causes approximately 10,000 deaths per year, mainly in Asia and Africa, with 95% of deaths occurring in Asia alone. Currently, the number of dog bite cases reported in Pakistan is alarming. Such cases are first seen mostly by general practitioners. The current narrative review was planned to assess the knowledge, attitude and practices of general practitioners as reported in the literature from different countries published between July 2016 and February 2021 regarding dog bite management. Articles were searched using Google, Google Scholar, Ovid, Eric and PubMed databases. Keywords used included rabies, dog bite, general practitioners, medical officers, knowledge, attitude and practices. A total of 7 studies comprising 875 participants were included. ---Continue